Curriculum Changing in Indonesia: Impacts and Solutions for Natural Science Teachers in Islamic Secondary School at Rejang Lebong Regency - Supardan, Dadan (Jurnal Pendidikan Tambusai, 2021)
Curriculum is a set of course or resources that useful to increase teaching and learning process. The national school curriculum has undergone many changes in the history of Indonesian education, including in the years 1947, 1952, 1964, 1968, 1975, 1984, 1994, 2004, 2006, and the most recent is 2013. The shift in the curriculum is targeted at improving schooling. The goal of this research is to recognize the issues of shifting education and address them namely impact of changing curriculum and solutions.This research was a qualitative study. The samples of this study were 10 Natural Science Teachers in Islamic Secondary School at Rejang Lebong Regency. The data was collected by using interview and analyzed by using qualitative way. The findings of this study were: Natural Science Teachers have difficulties in designing material, lesson plan, and assessment for the students. They are also having difficulties in doing and handling their administration job in the school. These problems can be solved by government and Natural Science Teachers itself. Government is hoped can make a new policy so Natural Science Teachers can do their job in classroom easily and effectively. For, Natural Science Teachers is hoped can learn about using ICT optimally in preparation, while teaching, and evaluation